2006
DOI: 10.1007/s11136-006-9006-2
|View full text |Cite|
|
Sign up to set email alerts
|

Health-related quality of life of firefighters and police officers 8.5 years after the air disaster in Amsterdam

Abstract: This study demonstrates that professional disaster assistance workers are at risk for a lower HRQoL, even after years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
1
11
0
2
Order By: Relevance
“…A further report on the same cohort found that exposed workers reported a significantly lower physical healthrelated quality-of-life (HRQoL) and vitality than nonexposed workers [22]. Exposed police officers also reported a lower mental HRQoL.…”
Section: Impact On Respondersmentioning
confidence: 90%
“…A further report on the same cohort found that exposed workers reported a significantly lower physical healthrelated quality-of-life (HRQoL) and vitality than nonexposed workers [22]. Exposed police officers also reported a lower mental HRQoL.…”
Section: Impact On Respondersmentioning
confidence: 90%
“…Furthermore, it may take much longer before their actions would be rewarded. Studies have shown that these distinctions may affect not only the way first responders perceive themselves and their occupation but also their tendency to develop assorted psychopathologies including PTSD (Brough, 2004; Basiñska and Wiciak, 2003; for review see Langan-Fox and Cooper, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Conditions such as post-traumatic stress disorder, depression, and chronic fatigue are reported in firefighters and police officers who have worked in disasters [10] Slottje et al [2] evaluated the QoL of firefighters and police officers exposed to a Dutch air disaster that had occurred 8.5 years before and concluded that these emergency responders exhibited decreased QoL, even after many years. Voelker et al [15] evaluated soldiers who worked in the first Gulf War and found that it persistently negatively impacted their QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the influence on the QoL of professionals who have worked in mass disasters [2] [7]. Firefighters and police officers are the most studied populations.…”
Section: Introductionmentioning
confidence: 99%